A Case Study of Agnikarma Therapy in the Management of Gridhrasi w.s.r. to Sciatica - Ninama, Divyabahen S.; Patel, Jigna; Panchal, Sonal; Parmar, Damini (Asian Journal of Pharmaceutical Research and Development, 2023)
Gridhrasi is a Shulpradhana Nanatmaja Vatavyadhi. According to Acharya Charaka, Stambha (stiffness), Ruka (pain), Toda (pricking sensation) and Spandana (twitching) are the signs and symptoms of Vataja Gridhrasi. Aruchi (anorexia), Tandra (drowsiness) and Gaurava (heaviness) are the additional symptoms of Vatakaphaja Gridhrasi. Sciatica is a major cause of illness among the working population in a developing country.It starts from hip and gradually comes down to waist, back, thigh, knee, shank and foot and affects these parts with stiffness, distress, piercing pain and with frequent quivering.In Ayurveda science, various modalities of treatment are explained for the management of Gridhrasi. Agnikarma Chikitsa is said to be superior.In modern medicine for the management of sciatica various modalities are available such as Conservative treatment, Epidural steroid injection, Peri-radicular infiltration and Surgical treatment.Purpose of the study was to evaluate the efficacy of Agnikarma therapy performed by Panch Dhatu Shalaka (five types of metals) in case of Sciatica. After giving Agnikarma sitting, we have got marked improvement in symptoms of Sciatica and also found moderately improvement in various clinical examinations of Sciatica like SLR, Cross SLR, Local tenderness etc.